Influence of Elevated Temperatures on Resistance Against Phoma Stem Canker in Oilseed Rape - Noel, Katherine; Qi, Aiming; Gajula, Lakshmi Harika; Padley, Craig; Rietz, Steffen; Huang, Yong-Ju; Fitt, Bruce D. L.; Stotz, Henrik U. (Frontiers in Plant Science, 2022)
Cultivar resistance is an important tool in controlling pathogen-related diseases in agricultural crops. As temperatures increase due to global warming, temperature-resilient disease resistance will play an important role in crop protection. However, the mechanisms behind the temperature-sensitivity of the disease resistance response are poorly understood in crop species and little is known about the effect of elevated temperatures on quantitative disease resistance. Here, we investigated the effect of temperature increase on the quantitative resistance of Brassica napus against Leptosphaeria maculans. Field experiments and controlled environment inoculation assays were done to determine the influence of temperature on R gene-mediated and quantitative resistance against L. maculans; of specific interest was the impact of high summer temperatures on the severity of phoma stem canker. Field experiments were run for three consecutive growing seasons at various sites in England and France using twelve winter oilseed rape breeding lines or cultivars with or without R genes and/or quantitative resistance. Stem inoculation assays were done under controlled environment conditions with four cultivars/breeding lines, using avirulent and virulent L. maculans isolates, to determine if an increase in ambient temperature reduces the efficacy of the resistance. High maximum June temperature was found to be related to phoma stem canker severity. No temperature effect on stem canker severity was found for the cultivar ES Astrid (with only quantitative resistance with no known R genes). However, in the controlled environmental conditions, the cultivar ES Astrid had significantly smaller amounts of necrotic tissue at 20°C than at 25°C. This suggests that, under a sustained temperature of 25°C, the efficacy of quantitative resistance is reduced. Findings from this study show that temperature-resilient quantitative resistance is currently available in some oilseed cultivars and that efficacy of quantitative resistance is maintained at increased temperature but not when these elevated temperatures are sustained for a long period.